Strategic Insights: Analyzing External Environment Affecting Private Oil Spill Response Company In Indonesia - Dwinanti, Pratiwi; Wijaya, Chandra (Pelopor Publikasi Akademika, 2024)
It is inevitable that the growth of the oil and gas industry becomes one of the most significant causes of environmental pollution. The increasing number of oil and gas exploration and production company and companies focusing in conservation of natural and environmental resources will inevitably become a dilemma that will be faced considering the potential impact of such activities. It is important for a private oil spill response company in Indonesia to understand market dynamics, comply with regulations, manage risks, and build a strategic position for a long-term success. This research is part of the type or type of qualitative research that is analytically descriptive in order to provide a complete picture of the occurrence or event being studied and to analyze how the variables being investigated relate to each other. Analyzing the external environment that affecting private oil spill response company in Indonesia improves the organization's capacity to mitigate risks, adjust to technological advancements, and preserve a competitive advantage. It also enables the company to maintain a higher level of customer and stakeholder engagement that essential to deliver effective and efficient services.